Unusual Presentation of Large Retroperitoneal Lipoma in a 3-Year-Old Child: A Case Report - Mesfin Wubishet; Betre Shimelis; Workye Tigabie; Ashenafi Lemma (Clinical Medicine Insights: Case Reports)
Background: Lipomas can occur almost anywhere in the body, but they are exceptionally rare in the retroperitoneal region. While lipomas are common in adults, they are quite uncommon in children. Even among adults, retroperitoneal lipomas are not frequently encountered. When symptomatic, retroperitoneal lipomas may present with abdominal swelling, pain, or constipation, as noted in previous literature. However, there have been no reported cases of retroperitoneal lipomas causing recurrent diarrhea in children. Case presentation: We present a rare case of a large retroperitoneal lipoma in a 3-year-old child who experienced recurrent diarrhea and intermittent abdominal pain for 2 months, without any urinary symptoms. All Laboratory investigations were within reference ranges for his age. A CT scan showed a large abdominal mass likely from the retroperitoneum, potentially a lipogenic tumor, though liposarcoma could not be excluded. The patient was successfully treated with complete surgical excision, and histopathological analysis confirmed the diagnosis of a benign lipoma. Conclusion: Retroperitoneal lipoma is a rare variant of lipoma in children, often presenting with various nonspecific and misleading symptoms. Due to the rarity of this condition and the limited awareness among clinicians, it frequently leads to misdiagnosis. Radiologic imaging, particularly CT and MRI scans, are essential diagnostic tools for identifying these tumors. This case report emphasizes the importance of maintaining a high index of suspicion for this rare condition when clinicians encounter recurrent diarrhea and concerning radiological findings. The characteristic behavior of retroperitoneal lipomas in children is still not well-defined; therefore, long-term follow-up is recommended.